Effects of holding postures on user-defined touch gestures for tablet interaction. Issue 141 (September 2020) - Tu, Huawei; Huang, Qihan; Zhao, Yanchao; Gao, Boyu
Highlights: A first study to examine the effects of holding postures on user-defined touch gestures for tablet interaction A quantitative and qualitative characterization of user-defined gestures for tablet interaction with bimanual and unimanual (palm, forearm) support postures Insights into users mental models when creating tablet gestures in both bimanual and unimanual support postures Guidance to tablet designers for designing gesture interfaces with bimanual or unimanual supports. Abstract: Multi-touch tablets afford various support positions and can accommodate interaction with the thumbs and multiple fingers from both hands. However, today's touch gesture design for tablets generally does not consider the effects of such a diversity of interactions. Therefore, we conducted a user-elicited study by asking participants to create touch gestures to perform interactive tasks in three common tablet-holding postures respectively (i.e. two-handed palm support, one-handed palm support and one-handed forearm support). In all, 1323 gestures for 30 common tasks were logged and analyzed. Our main findings are: (1) In general, user-designed gestures were quite alike for one-handed palm support and forearm support; (2) for commands such as target-position-related ones (e.g. "select single or group (center area of the screen)") and target-movement-related ones (e.g. "move a lot (left to right) / (right to left)" and "move a little (center area of the screen)"), two-handed support and one-handed supports led to different user-defined gesture performances; (3) the effects of tablet holding postures on users' mental models varied in referents being executed by defined gestures. We also present a complete user-defined gesture set, quantitative agreement rates and practical implications for gesture design on tablets.